Stakeholder mapping as a transdisciplinary exercise for jaguar conservation in the Brazilian Atlantic Forest. Issue 5 (16th March 2022) - Sandroni, Laila Thomaz; de Barros Ferraz, Katia Maria Paschoaletto Micchi; Marchini, Silvio; Percequillo, Alexandre; Coates, Robert; Paolino, Roberta Montanheiro; Barros, Yara; Landis, Mariana; Ribeiro, Yuri Geraldo Gomes; Munhoes, Leticia Prado
Abstract: Transdisciplinary projects are fundamental to a more effective and just conservation, but their application and coherent framing present challenges, since their nature is to bring together different epistemological backgrounds and world views. This paper identifies the possibilities offered by stakeholder mapping as a tool for generating common understandings in transdisciplinary conservation research projects. Lessons are drawn from experiential learning through the case of jaguar conservation in the Brazilian Atlantic Forest (BAF). Stakeholder mapping proved to be an essential diagnostic tool that generated an overview of the material context of human–jaguar interactions in the BAF to stakeholders engaged in the project. The process and overview drew attention to gaps in stakeholder knowledge that need to be addressed to enhance conviviality between humans and jaguars in fragmented landscapes. Recognizing these knowledge gaps assists in the production of methodologies that can effectively encompass different social groups, and increase all parties' perceptions of the legitimacy of conservation activities. We argue that, due to its collective nature, stakeholder mapping can foster mutual learning and deeper communication in the context of divergent framings of complex nature conservation problems, such as in jaguar conservation. Abstract : This article aims at identifying limits and possibilities of stakeholder mapping as a tool for generating common understandings in transdisciplinary research projects in conservation. The lessons are drawn from experiential learning trough the study case of Jaguar conservation in the Brazilian Atlantic Forest.